DNA sequences homologous to hepatitis C virus (HCV) in the extrachromosomal circular DNA in peripheral blood mononuclear cells of HCV-negative subjects - Dennin, Reinhard H.; Wo, Jian-er (Journal of Zhejiang University. B. Science, 2019)
Objective This study aimed to investigate DNA sequences that are substantially homologous to the corresponding RNA sequence sections of the hepatitis C virus (HCV). These DNA sequences are present in the whole DNA extracted from peripheral blood mononuclear cells (PBMCs) of HCV-negative subjects. We presumed that these experimentally proven 5′-noncoding region (5′-NCR) homologous DNA sequences could be contained in the extrachromosomal circular DNA (eccDNA) fraction as part of the whole cellular DNA. Methods Home-made polymerase chain reaction (PCR) with whole cellular and isolated eccDNA, nucleotide basic local alignment search tool (BLASTn) alignments, and tests for patterns of methylation in selected sequence sections were performed. Results The PCR tests revealed DNA sequences of up to 320 bp that broadly matched the corresponding sequence sections of known HCV genotypes. In contrast, BLASTn alignment searches of published HCV 5′-NCR sequences with human genome databases revealed only sequence segments of up to 36 bp of the 5′-NCR. The composition of these sequences shows missing base pairs, base pair mismatches as well as complete homology with HCV reference sequences. These short sequence sections are present in numerous copies on both the same and different chromosomes. The selected sequence region within the DNA sequences of the 5′-NCR revealed a broad diversity of individual patterns of methylation. Conclusions The experimental results confirm our assumption that parts of the HCV 5′-NCR genomic RNA sequences are present at the DNA level in the eccDNA fraction of PBMCs. The tests for methylation patterns therein revealed individual methylomes which could represent an epigenetic feature. The respective sequence section might be subject to genetic regulation.